Food and nutrition security definitions, constructs, frameworks, measurements, and applications: global lessons - Rafael Pérez-Escamilla (Frontiers Media S.A., 2024)
Food security (FS) is a powerful social determinant of health (SDOH) and is crucial for human and planetary health. The objectives of this article are to (i) provide clarity on the definitions of FS and nutrition security; (ii) provide a framework that clearly explains the links between the two constructs; (iii) summarize measurement approaches, and (iv) illustrate applications to monitoring and surveillance, policy and program design and evaluation, and research, mainly based on the ongoing rich experience with food insecurity (FI) scales. A clear and concise definition of FI and corresponding frameworks are available. There are different methods for directly or indirectly assessing FI. The best method(s) of choice need to be selected based on the questions asked, resources, and time frames available. Experience-based FI measures disseminated from the United States to the rest of the world in the early 2000s became a game changer for advancing FI research, policy, program evaluation, and governance. The success with experience FI scales is informing the dissemination, adaptation, and validation of water insecurity scales globally. The many lessons learned across countries on how to advance policy and program design and evaluation through improved FS conceptualization and measurement should be systematically shared through networks of researchers and practitioners.